Стародавнє залізодобування і гірнича справа в Свєнтокшиських горах (Південна Польща) - Біленін, К. (Археологія, 2000)
У статті висвітлено основні результати багаторічних досліджень найпотужнішого у Середній Європі центру чорної металургії останньої чверті І тис. до н. е. — першої половини І тис. н. е. Розглянуто питання, пов’язані з історією та методикою вивчення пам'яток стародавнього залізодобування й гірничої справи, техніки і технології чорної металургії, організації виробництва і збуту «свєнтокшиського» заліза. Статья посвящена итогам многолетних полевых и лабораторных исследований широко известного в европейской специальной литературе центра черной металлургии рубежа первой половины I тыс. н. э. в Свентокшиских горах, оставленного племенами позднелатенской и пшеворской культур. Рассмотрены вопросы истории и методики изучения памятника, становления и развития техники и технологии производства железа в указанном регионе, углежжения и рудодобычи. Особое внимание уделено социально-экономическим и культурноисторическим аспектам в развитии железоделательного ремесла. Определено место Свентокшиского центра черной металлургии среди синхронных ему памятников древней европейской железодобычи. The paper presents the totals of the many-year field and laboratory studies of the center of ferrous metallurgy, which is well known in the European special literature and is related to tribes of the late La Tene and Pszewor cultures, at the boundary of the first half of the 1st mill. AD in the Swientokrziskie Mountains. The questions of the history and the methods of study of the monument, formation, and development of the technique and technology of iron-making in the region indicated, charring, and ore mining are considered. A special attention is paid to the social-economic and cultural-historical aspects of the development of the iron-making craft, and the place of the Swientokrziski center of ferrous metallurgy among synchronous monuments of ancient European iron mining is determined.